Connection assembly for steel-foam concrete composite light-weight panels - experimental study - Prabha, P.; Kumar, V. Ramesh; Marimuthu, V.; Palani, G.S. (Journal of Structural Engineering, 2024)
In this paper, a simplified prefabricated connection assembly is developed to act as a splice between top and bottom Steel-Foam Concrete Composite (SFCC) wall panel and also to connect with SFCC floor/roof panel at roof level of the building. The components of the connection assembly are SFCC connecting panel, top and bottom seat angles and bolts. SFCC connecting panel joins the top and bottom SFCC wall panel and is then connected to SFCC floor/roof panel by top and bottom seat angle connection by using bolts. The developed connection assembly is so devised that it develops rotational stiffness as sum of flexural stiffness of the wall panels and the floor/roof panel. The flexural stiffness of both the top and bottom wall panels is initiated by contact bearing of the both panels against SFCC panel in the connection assembly, whereas, the flexural stiffness of floor/roof panel is initiated by using top and bottom seat angle connection. In order to verify the flexural stiffness participation of the connection and the connected components, an experimental study is conducted on an exterior SFCC wall to floor joint, which utilizes the aforementioned connection. The failure is due to the plastic hinge formation in the mid span of SFCC floor/roof panel at the ultimate load of 107 kN. The connection possesses moment carrying capacity higher than the floor/roof panel capacity and is found to be adequate to be effectively used in buildings.